(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2021)
In Bangladesh, numerous tribal people of Chittagong Hill Tracts have been using different parts of Thysanolaena maxima Roxb. for many years. The present study was designed to investigate CNS depressant and analgesic activities of methanol extract of the aerial parts of the plant in mice models. CNS depressant activity of the crude extract (200 and 400 mg/kg) was evaluated using open field, hole cross and thiopental-induced sleeping time tests using diazepam as the standard. Analgesic activity was determined using acetic acid-induced writhing and hot plate tests using diclofenac sodium as the standard. The extract showed dose dependent suppression of locomotion in open field and hole cross tests and exerted sedative action in thiopental induced sleeping time. In the open field and the hole-cross tests, maximum CNS depressant activity was observed at 90 min after administration of extract and the standard drug. The extract significantly induced the onset of sleep and prolonged the sleeping time in thiopental induced sleeping test compared to the control group. The extract produced significant (p < 0.05) analgesic activity by inhibiting writhing by 41.89% and 60.81%, at doses of 200 and 400 mg/kg body weight, respectively, which was comparable to the inhibition of diclofenac sodium (73.64%). Additionally, in hot plate test, the extract exhibited a significant (p < 0.05) increase in pain threshold in a dose dependent manner. The findings of the study are encouraging and demands further investigation of other bioactivities with isolation of pure compounds. Dhaka Univ. J. Pharm. Sci. 20(2): 227-233, 2021 (December)